Crack-free high quality 2 μm-thick Al0.5Ga0.5N grown on a Si substrate with a superlattice transition layer. Issue 7 (17th December 2019) - Huang, Yingnan; Liu, Jianxun; Sun, Xiujian; Zhan, Xiaoning; Sun, Qian; Gao, Hongwei; Feng, Meixin; Zhou, Yu; Ikeda, Masao; Yang, Hui
Abstract : We reported the successful growth of a crack-free high-quality 2 μm-thick Al0.5 Ga0.5 N film with a smooth surface grown on planar Si by metal–organic chemical vapor deposition. Abstract : The utilization of Si substrates to fabricate AlGaN-based deep ultraviolet (DUV) light-emitting diodes (LEDs) is deemed as an effective way to improve light extraction efficiency with the thin-film flip-chip architecture, which calls for crack-free high-quality high Al-content AlGaN films grown on Si. In this study, we reported the successful growth of a crack-free high-quality 2 μm-thick Al0.5 Ga0.5 N film grown on planar Si by metal–organic chemical vapor deposition. A smooth surface with a root-mean-square roughness of 1.5 nm was obtained by employing a superlattice transition layer. Double crystal X-ray rocking curves yielded full widths at half maximum of 499 and 648 arcsec for the Al0.5 Ga0.5 N (0002) and (101̄2) reflection planes, respectively, revealing a low threading dislocation density of 3.8 × 10 9 cm −2 . This work paves the way for the realization of cost-effective high-performance AlGaN-based DUV LEDs and photodetectors grown on a Si platform.